Isolation, Extraction, Purification, and Molecular Characterization for Thermostable α-Amylase from Locally Isolated Bacillus Species in Sudan - Rakaz, Maha A.; Hussien, Mohammed O.; Ibrahim, Hanan M. (Biochemistry Research International, 2021)
The aim of this study was to isolate some soil bacteria strain that produced α-amylase and subsequent extraction and purification. One hundred soil samples were collected from different geographical areas in Khartoum State such as north Omdurman, Toti Island, and Soba. Samples were analyzed for starch hydrolyzing bacteria. Among several bacteria isolated, Bacillus cereus and Bacillus licheniformis were identified as active α-amylase producers. Both bacteria showed a large zone of clearance of 20 mm when grown on starch-agar plates. The identity was conducted using biochemical characterization and confirmed by sequencing their 16S-rDNA. The constitutive nature of amylase was proved by amplification of the amylase gene from the genome of B. licheniformis. The α-amylase activity from the spent medium of B. cereus and B. licheniformis was optimized at pH 8.0 and temperature of 45°C and 65°C, respectively. The α-amylase produced by both bacteria is alkalophilic and thermophilic. The experiments confirmed that B. licheniformis can be a good source of amylase for industrial applications in Sudan.